The effect of myrtus communis l. extract on nephrolithiasis model in rats - ERTAŞ, BÜŞRA; ŞEN, ALİ; ŞENER, TARIK EMRE (My University, 2023)
Objective: Nephrolithiasis is a common urological disease that can lead to renal failure. Oxidative stress has been shown to be a contributing factor for nephrolithiasis and many agents have been studied to prevent and treat oxidative stress-related nephrolithiasis and renal damage. Myrtus communis (MC) extract has been shown to be an important antioxidant in different animal models. In this study, myrtus communis (MC) extract was administered preventively or therapeutically to rats with kidney stones, and its effectiveness was investigated. Materials and metods: Wistar albino rats were divided into 4 groups (n=8); control (C), ethylene glycol (EG), EG+preventive MC, and EG+curative MC groups. The nephrolithiasis model was created by adding 0.75% EG to drinking water for 8 weeks. Ultimately, 24-hour urine was collected to measure calcium, citrate, and creatinine levels. After decapitation, kidney tissues were harvested for histological analyses, measurement of osteopontin and 8-hydroxydeoxyguanosine (8-OHdG) levels, and N-acetyl-β-glucosaminidase (NAG), myeloperoxidase (MPO) and caspase-3 activities. Results: In 24-hour urine samples, calcium, citrate and creatinine levels were decreased in the EG group, while oxalate levels were increased and in treatment groups these parameters returned to control levels. MPO, 8-OHdG, caspase-3 and NAG activity were significantly increased in tissue and these changes were reversed in both MC groups. Histological findings also supported the biochemical parameters. Conclusion: Myrtus communis can reduce oxidative stress and histopathological changes in kidney tissues in rat nephrolithiasis model when used as either a preventive or therapeutic agent. If supported with further clinical trials, MC might have clinical implications in preventing oxidative renal cell injury and ultimately kidney stone formation.

Giriş / Amaç: Nefrolitiazis böbrek yetmezliğine yol açabilen yaygın bir ürolojik hastalıktır. Oksidatif stresin böbrek taşı oluşumuna katkıda bulunan bir faktör olduğu gösterilmiştir ve oksidatif strese bağlı böbrek taş oluşumunu ve böbrek hasarını önlemek ve tedavi etmek için birçok ajan üzerinde çalışılmıştır. Myrtus communis (MC) ekstresinin farklı hayvan modellerinde önemli bir antioksidan olduğu gösterilmiştir. Bu çalışmada Myrtus communis (MC) ekstresi böbrek taşı oluşturulan sıçanlara koruyucu veya tedavi edici uygulanarak etkinliği araştırıldı Materyal ve Metod: Wistar albino türü sıçanlar 4 gruba ayrıldı (n=8); kontrol (C), etilen glikol (EG), EG+koruyucu MC, EG+küratif MC grupları. Nefrolitiazis modeli 8 hafta boyunca içme suyuna %075 EG eklenerek oluşturulmuştur. Deney sonunda, kalsiyum, sitrat ve kreatinin düzeylerini ölçmek için 24 saatlik idrar toplandı. Dekapitasyon sonrasında histolojik analizler, osteopontin ve 8-hidroksideoksiguanozin (8-OHdG) düzeyleri ve N-asetil-β-glukosaminidaz (NAG), miyeloperoksidaz (MPO) ve kaspaz-3 aktivite tayinleri için böbrek dokuları çıkarıldı. Bulgular: 24 saatte toplanan idrar örneklerinde EG verilen tedavisiz grupta kalsiyum, sitrat ve kreatinin seviyeleri düşerken oksalat seviyeleri yükselmiş ve tedavi gruplarında bu parametreler kontrol seviyelerine dönmüştür. EG grubunda dokuda ise MPO ve 8-OHdG düzeyleri, kaspaz-3 ve NAG aktiviteleri önemli ölçüde artarken bu değişiklikler her iki MC grubunda da geriye döndü. Histolojik değerlendirmeler de biyokimyasal parametreleri destekledi. Sonuç: Myrtus communis, gerek koruyucu ve gerekse tedavi edici bir ajan olarak kullanıldığında, sıçan nefrolitiazis modelinde böbrek dokularındaki oksidatif stresi ve histopatolojik değişiklikleri azaltabilir. Daha ileri klinik deneylerle desteklenirse, MC'nin oksidatif böbrek hücre hasarını ve nihayetinde böbrek taşı oluşumunu önlemede klinik etkileri olabilir. (NCI-2022-12-14)
Myrtus communis l. ekstraktının sıçanlarda nefrolitiazis modelinde etkisi
Keywords: Ethylene glycol; Renal insufficiency; Oxidative stress; Nephrolithiasis; Hyperoxaluria; Etilen glikol; renal yetmezlik; oksidatif stres; nefrolitiazis; hiperoksalaüri